Clomipramine counteracts lipid raft disturbance due to short-term muscle disuse. (18th January 2018) - Bryndina, Irina G.; Shalagina, Maria N.; Sekunov, Alexey V.; Zefirov, Andrei L.; Petrov, Alexey M.
Highlights: Hindlimb suspension (HS) for 12 h changes membrane properties in soleus muscle. We try to prevent 12 h of HS-induced raft disturbance by clomipramine pretreatment. Clomipramine prevents ceramide accumulation and cholesterol loss after 12 h of HS. Clomipramine counteracts loss of raft integrity in junctional region after 12 h of HS. Abstract: Disuse-induced skeletal muscle dysfunction is a serious consequence of long-term spaceflight, numerous diseases and conditions for which treatment possibilities are still strictly limited. We have previously shown that acute hindlimb suspension (HS)-mediated disuse disrupts membrane lipid rafts in the unloaded muscle. Here, we investigated whether pretreatment of rats with the inhibitor of acid sphingomyelinase, clomipramine (1.25 mg/g/day, intramuscularly, for 5 days before HS), is able to hinder the loss in lipid raft integrity in response to 12 h of HS. Clomipramine pretreatment significantly counteracted the decrease in labeling of the plasma membranes with lipid raft markers (fluorescent cholera toxin B subunit and bodipy-GM1-ganglioside) specifically in the junctional regions of the suspended soleus muscle. This was associated with: a) enhancing raft disrupting potential of exogenous sphingomyelinase in the junctional membranes; b) prevention of both ceramide accumulation and cholesterol loss; c) prevention of decline in nicotinic acetylcholine receptor labeling in the unloaded muscle. Our data suggest that sphingomyelinase-mediated raft disturbance serves as one of the earlier events in HS effects.